PATTERN OF POTASSIUM RELEASE FROM SLOW RELEASE FERTILIZER POTASSIUM CLORIDE-BENTONITE FERTILIZER - Carver J M; Suarya P; Irdhawati Irdhawati (Program Magister Pendidikan IPA, Program Pascasarjana Universitas Cenderawasih, 2023)
Potassium has an important role in the process of plant growth, but its presence and availability in the soil are limited, because potassium is easily lost and flows out by water. Increasing the efficiency of potassium fertilization can be pursued through the formulation of fertilizer in the form of slow-release fertilizer (SRF) using bentonite. This study aimed to determine the release of potassium in potassium chloride fertilizer into the soil after bonding with acid-activated bentonite coated with potassium chloride. The composition of the KCl fertilizer made varies with bentonite with a mass ratio (g) of 1:1; 2:1; 3:1; 4:1; and 5:1, with a percolation time of 28 days. The concentration of released potassium was determined using an atomic absorption spectrophotometer. Material characterization was carried out by FTIR. The results showed that the ratio 1:3 had the highest potassium content of 45.12% with an incubation time of 28 days. The concentration of released potassium on day 7; 14; 21; and 28 respectively (12.55±1.25)%, (28.39±1.49)%, (5.,91±0.98)%, and (70.49±1.36)% . The results of the characterization of the determination of the fungal group on SRF3 were not significantly different from that of activated bentonite. Even though there were differences in the intensity of certain peaks and changed the functional groups.